2005
DOI: 10.1007/s10526-004-5546-y
|View full text |Cite
|
Sign up to set email alerts
|

Field assessment in land of origin of host specificity, infestation rate and impact of Ceratapion basicorne a prospective biological control agent of yellow starthistle

Abstract: Yellow starthistle, Centaurea solstitialis (Asteraceae), is an important invasive alien weed in the western United States. Currently established biological control agents attack only the capitula (flowerheads), and are not effectively controlling the plant in much of its range. The geographic center of diversity for the plant appears to be in Turkey, but no agents have been introduced from this country. Ceratapion basicorne (Coleoptera: Apionidae) is common in Central Turkey, attacking 25-100% of yellow starth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…cyanus L., and Cnicus benedictus L., which suggests that it is highly host-speciWc (Alonso-Zarazaga, 1990a;Wanat, 1994;Campobasso et al, 1999). The insect is common on yellow starthistle in Turkey, Greece, and Georgia (Rosenthal et al, 1994;Balciunas, 1998;Uygur et al, 2005) and is widely distributed in Europe and western Asia (Alonso-Zarazaga, 1990a;Wanat, 1994). Overwintering adults become active in the early spring and feed on rosette leaves (Clement et al, 1989).…”
Section: Life History and Behavior Of Ceratapion Basicornementioning
confidence: 99%
See 1 more Smart Citation
“…cyanus L., and Cnicus benedictus L., which suggests that it is highly host-speciWc (Alonso-Zarazaga, 1990a;Wanat, 1994;Campobasso et al, 1999). The insect is common on yellow starthistle in Turkey, Greece, and Georgia (Rosenthal et al, 1994;Balciunas, 1998;Uygur et al, 2005) and is widely distributed in Europe and western Asia (Alonso-Zarazaga, 1990a;Wanat, 1994). Overwintering adults become active in the early spring and feed on rosette leaves (Clement et al, 1989).…”
Section: Life History and Behavior Of Ceratapion Basicornementioning
confidence: 99%
“…However, absence of reports of the development of this insect from these hosts in the Weld (Alonso-Zarazaga, 1990a;Wanat, 1994;Campobasso et al, 1999;Uygur et al, 2005) prompted me to further evaluate its host speciWcity. The purpose of the present study was to determine what non-target plants are susceptible to damage by C. basicorne and to measure the relative amount of damage the insect can cause under no-choice laboratory conditions.…”
Section: Life History and Behavior Of Ceratapion Basicornementioning
confidence: 99%
“…Field observations (Uygur et al , ) and modelling analysis (Gutierrez et al , ) suggest that natural enemies killing whole plants before seed maturation and/or reducing the ability of surviving plants to compensate for feeding damage with reduced seed production are required for successful control (see below). The weevil Ceratapion basicorne (Illiger) (Coleoptera; Brentidae) attacks the rosette stage of YST throughout most of its range in the Mediterranean Basin (Alonso‐Zarazaga, ; Antonini et al , ) and has some of requisite attributes: infestation levels range from 25% to 100% (Uygur et al , ; Smith et al , ) and it is highly host specific (Smith et al , ; Smith, , ; Rector et al , ; Cristofaro et al , ). A release permit application for C. basicorne for North America was submitted to USDA‐APHIS (U.S. Department of Agriculture's Animal and Plant Health Inspection Service) on 26 January 2006 (Smith, ), although approval has not been granted because of concerns about possible risk to safflower crops ( Carthamus tinctorius ) and the ornamental cornflower ( Centaurea cyanus ) that are of Palearctic origin (Hinz et al , ; L. Smith, personal communication).…”
Section: Introductionmentioning
confidence: 99%
“…Rosenthal et al () reported 50–97% infestation and Smith et al () reported 48–100% infestation in field garden studies, whereas Balciunas and Korotyaev () found an average 58% infestation across 20 sites. Uygur et al () reported that at least 50% of the root crown area was damaged in 63% of YST plants in southern Turkey. The number of larvae per plant was positively correlated with root diameter, with aggregation occurring both among plants and within plants (Balciunas & Korotyaev, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation